THE TYPES OF DIRECTNESS AND INTERNAL MODIFICATION ON REQUEST STRATEGIES: A PRAGMATIC STUDY - Agustia, Km Tri Sutrisna; Putri, Ni Luh Gede Mega (LITERA : Jurnal Bahasa Dan Sastra, 2020)
ABSTRACTIn making interaction with the guests in the restaurant, the way the restaurant’s staffs uttered theirintentions were matter because it would give the impression of their services to the guests.Therefore, this article aimed to find out the types of directness in request strategies which wereused by Chandi restaurant’s staffs and also to classify the types of internal modification in thosestrategies. In analyzing the data, this study applied the descriptive qualitative approach. Thetheory used were Blum-Kulka, House and Kasper (1989) and Sifianou (1999). It is found that thetypes of directness in request strategy that were used by Chandi restaurant’s staffs are directstrategy and conventionally indirect strategy and also the types of internal modification thatoccurred in the conversation were the openers, softeners, and fillers modification types.Keywords: types of directness, internal modification, request strategy.ABSTRAKKetika berinteraksi dengan para tamu di restoran, cara dari staff restoran menyampaikan niatmereka itu penting karena hal tersebut akan memberikan kesan bagaimana pelayanan merekakepada para tamu. Oleh karena itu, artikel ini bertujuan untuk mengetahui jenis dariketerusterangan dalam strategi permintaan yang digunakan oleh staff restoran Chandi dan jugauntuk mengklasifikasikan jenis modifikasi internal dalam strategi tersebut. Dalam menganalisisdata, penelitian ini menggunakan pendekatan deskriptif kualitatif. Teori yang digunakan adalahteori Blum-Kulka, House and Kasper (1989) dan Sifianou (1999). Dapat diketahui bahwa jenisjenisketerusterangan dalam strategi permintaan yang digunakan oleh staff restoran Chandiadalah strategi langsung dan strategi tidak langsung konvensional dan juga jenis-jenismodifikasi internal yang digunakan dalam percakapan adalah jenis pembuka, pelembut, danjenis modifikasi pengisi.Kata Kunci: jenis keterusterangan, modifikasi internal, strategi permintaan.